PENERAPAN PURSED LIPS BREATHING DAN PROGRESSIVE MUSCLE RELAXATION TERHADAP TINGKAT KELELAHAN (FATIGUE) PADA PASIEN CHRONIC KIDNEY DISEASE (CKD) DI RUANG RAWAT INAP ABDURAHMAN BIN AUF 2 RSUD AL-IHSAN BANDUNG - Fauzi Ridwanul Hakim; Ida Rosdiana; Yanti Cahyati (Tasikmalaya Nursing Journal, 2026)
ABSTRACT Background: Chronic Kidney Disease (CKD) is a progressive condition characterized by structural and functional changes in the kidneys due to various causes. One common symptom experienced in Chronic Kidney Disease (CKD) is fatigue. One non-pharmacological approach to addressing fatigue is relaxation therapy, namely Pursed Lips Breathing and Progressive Muscle Relaxation (PMR). Research Objective: The Purpose this scientific paper aims to elucidate the implementation of Pursed Lips Breathing and Progressive Muscle Relaxation on fatigue levels in Chronic Kidney Disease (CKD) patients in the Abdurahman Bin Auf 2 Ward of Al-Ihsan Regional General Hospital in Bandung Methodology: The method used in this scientific paper is quantitative, which is a case study approach involving 2 respondents regarding nursing issues related to fatigue. Research results: for 3 days with a frequency of once a day. The evaluation conducted on the first day before the therapy indicated that patient 1 was at a scale of 26, while after the application, the scale value decreased to 20, which means it is below <22, thus categorized as no fatigue. Meanwhile, patient 2, who initially was at a scale of 28, saw the scale value decrease to 21 after the application of Pursed Lips Breathing and Progressive Muscle Relaxation (PMR), also below <22, categorized as no fatigue.